By rule, log(MN) = logM + log N
So, log 26 = log(2x13) = log 2 + log 13 = a + b
2006-12-17 11:46:50
·
answer #1
·
answered by Ethan 2
·
0⤊
0⤋
26 = 2 * 13
so log 26 = log (2*13)
according to the power property (log xy = log x + log y)
we get log 26 = log 2 + log 13.
log 2 = a and log 13 = b, so
log 26 = a + b
Hope that helps!
2006-12-17 11:46:30
·
answer #2
·
answered by laffytaffychick13 1
·
0⤊
0⤋
log 26 = log (2*13) = log 2 + log 13 = a + b
2006-12-17 11:49:31
·
answer #3
·
answered by imamulleith 2
·
0⤊
0⤋
log 2+log 13=log(2*13)=log 26 Ans.
2006-12-17 11:50:08
·
answer #4
·
answered by aminnyus 2
·
0⤊
0⤋
log 2=a
log 13=b
log 26=log 13 + log 2=a+b
2006-12-17 11:50:28
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
Log 26 will surely be a+b?
2006-12-17 11:46:03
·
answer #6
·
answered by PhD 3
·
0⤊
0⤋
log(26) = log(2 * 13) = log2 + log13 = a + b
2006-12-17 17:52:24
·
answer #7
·
answered by James Chan 4
·
0⤊
0⤋
undergo in ideas log (XYZ)=log(X)+log(Y)+log(Z) and log{(x)^y}=ylogx. log12=log(4*3)=log4+log3 =log(2^2)+log3 =2log2+log3=2a+b log18=log(2*3*3)=log2 +2 log3=a+2b log(4/3)=log(2*2) - log(3)=2a - b
2016-12-11 11:06:45
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
a+b = log 26
log x + log y = log(x*y)
2006-12-17 11:50:14
·
answer #9
·
answered by vertigosr37 1
·
0⤊
0⤋
i love you
2006-12-17 11:45:58
·
answer #10
·
answered by white clouds 1
·
0⤊
0⤋